2018
DOI: 10.17738/ajes.2017.0015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of recent seismicity in different parts of the Vlora-Lushnja-Elbasani-Dibra Transversal Fault Zone, Albania

Abstract: Spatial and temporal evaluation of current seismic activity throughout the Vlora-Lushnja-Elbasani-Dibra (VLED) transversal fault zone were carried out at the beginning of year 2016. The seismotectonic b-value, fractal dimension Dc-value and precursory seismic quiescence Z-value are considered for a detailed statistical analysis. Completeness magnitude Mc-value varies from 2.5 to 2.7 for different parts of the VLED fault zone. The b-value is calculated as 1.10±0.04 for the south western part and 1.13±0.05 for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The Grassberger and Procaccia (1983) correlation dimension calculation method or sphere counting method is among the extensively used method to study space time characteristics of earthquake activity. It is based on power law and is used for spatio-temporal studies on the space-time characteristics of earthquake activity for various parts of the world (Oncel and Wilson, 2007;Ormeni et al, 2017;Pailoplee and Choowong, 2014;Roy et al, 2011). In this method the correlation integral function is defined as:…”
Section: Methodsmentioning
confidence: 99%
“…The Grassberger and Procaccia (1983) correlation dimension calculation method or sphere counting method is among the extensively used method to study space time characteristics of earthquake activity. It is based on power law and is used for spatio-temporal studies on the space-time characteristics of earthquake activity for various parts of the world (Oncel and Wilson, 2007;Ormeni et al, 2017;Pailoplee and Choowong, 2014;Roy et al, 2011). In this method the correlation integral function is defined as:…”
Section: Methodsmentioning
confidence: 99%
“…The Elbasani fault zone is expressed by the diaper dome of Dumrea, Quaternary depression of Elbasani, and transversal structure of Labinoti. Analyses of spatial and temporal characteristics of the earthquake activity may supply significant clues for revealing the future seismic hazard along the VLED fault zone, and these anomaly regions may be interpreted as the locations of the next possible earthquakes [10]. Historical seismicity indicated that Elbasan has been destroyed by strong earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter tells us about the structure and features of the Earth's crust in an area in which earthquakes occurred. It is related to the type of rocks, how they are arranged, and their ductility under stress (Aki 1965;Wyss 1973;Fytikas 1980;Katsumata 2006;Utsu 1971;Bayrak, Öztürk 2004;Polat et al 2002;Öztürk, Bayrak 2012;Öztürk 2011;Ormeni et al 2017;Nanjo 2020;Ormeni et al 2022). However, the correlation between heat flow data and seismic b-value has not been studied intensively for different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation between heat flow data and seismic b-value has not been studied intensively for different parts of the world. There are few studies for spatial and temporal evaluation of the b-value for different parts of Albania (Aliaj et al 2010;Ormeni 2015;Ormeni et al 2017;Özturk, Ormeni 2021). However, the correlation between the heat flow density and seismotectonic b-value was not studied for different zones of Albania.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation